The Effect of Neuropathic Pain Symptoms on Remission in Patients with Early Rheumatoid Arthritis - Salaffi, Fausto; Di Carlo, Marco; Carotti, Marina; Sarzi-Puttini, Piercarlo (Current Rheumatology Reviews, 2019)
Background: The presence of neuropatic pain (NeP) is common in subjects with established Rheumatoid Arthritis (RA), and it can influence the disease remission. These aspects have not been investigated in patients with Early Rheumatoid Arthritis (ERA). Objective: To investigate the effect of NeP on the achievement of remission in patients with ERA. Method: The study involved consecutive ERA patients with moderate or high disease activity. The painDETECT Questionnaire (PDQ), the 36-item Short Form Health Survey (SF-36), and the Euro- QoL-5 Dimensions (EQ-5D) were administered to all the patients, and their co-morbidity data were used to calculate their modified Rheumatic Disease Comorbidity Index (mRDCI). After six months’ follow-up, the presence or otherwise of NeP in each individual patient was calculated, and whether or not the Boolean remission criteria were satisfied. Results: The study was completed by 115 patients (76% females) whose PDQ scores indicated that 13% had probable NeP. At the end of the follow-up period, 25 patients (21.7%) met the Boolean remission criteria. Logistic regression analysis showed that baseline PDQ scores (p=0.0023) and the mRDCI (p=0.0054) were the strongest predictors of not being in Boolean remission. Only one of the 15 patients with concomitant NeP achieved Boolean remission. Conclusion: The presence of NeP may affect the achievement of remission in ERA patients. The PDQ can be a useful tool to measure central pain sensitisation in such patients.
Keywords: remission